Capabilities-based forecasting model for innovation development in small-and-medium construction firms (SMCFS) - Wang, Chen; Lee, Yee Lin; Yap, Jeffrey Boon Hui; Abdul-Rahman, Hamzah (Journal of Civil Engineering and Management, 2018)
Triggering innovation among Small-and-Medium Construction Firms (SMCFs) is of paramount importance to gear up the growth of construction firms. Thus, this study aims to develop a Capability-Based forecasting model for innovation development in SMCFs. Built on 157 questionnaires, the model was tested using partial least squares (PLS) technique of structural equation modelling (SEM). The practicality and robustness of this model was then validated by 12 experts. Findings affirm SMCFs making use of multiple Capability-Based approaches would be able to secure their performance via innovation activities. For academia, the new model contributes to the stream of construction innovation management by integrating both technological and organizational innovations in a single framework. For practitioners and policymakers, the model offers valuable input for continuing growth of SMCFs via innovation.